Successful BCMA CAR-T Therapy for Multiple Myeloma With Central Nervous System Involvement Manifesting as Cauda Equina Syndrome—A Wandering Road to Remission - Wang, Yiyun; Wang, Linqin; Zeng, Yifan; Hong, Ruimin; Zu, Cheng; Yin, Elaine Tan Su; Zhao, Houli; Wei, Guoqing; Yang, Li; Jin, Aiyun; Hu, Yongxian; Huang, He (Frontiers in Oncology, 2021)
Multiple myeloma (MM) with central nervous system (CNS) involvement is rare with only 1% incidence. So far, there is no standard or effective treatment for CNS MM, and the expected survival time is fewer than 6 months. Here, we report a case of MM with CNS involvement presented with cauda equina syndrome (CES) who achieved complete remission after anti-B-cell maturation antigen (BCMA) chimeric antigen receptor T (CAR-T) cell therapy (Chictr.org.cn, ChiCTR1800017404). The expansion of BCMA CAR-T cells was observed in both peripheral blood (PB) and cerebrospinal fluid (CSF). The CAR-T cells peaked at 2.4 × 106/l in CSF at day 8 and 4.1 × 109/l in PB at day 13. The peak concentration of interleukin (IL)-6 in CSF was detected 3 days earlier, and almost five times higher than that in PB. Next, morphological analysis confirmed the elimination of nucleated cells in CSF 1 month after CAR-T cell treatment from 300 cells/μl, and the patient achieved functional recovery with regressed lesion shown in PET-CT. The case demonstrated that BCMA CAR-T cells are effective and safe in this patient population.